1954
DOI: 10.1084/jem.100.5.425
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Egg Yolk in Diets on Anaphylactic Arthritis (Passive Arthus Phenomenon) in the Guinea Pig

Abstract: Whole egg yolk incorporated as a supplement in the diet of baby guinea pigs afforded protection against anaphylactic arthritis as determined: (a) by measurement of joint swelling; (b) by the rise in serum level of some substance which reacts with diphenylamine; (c) by histologic examination. The active material in egg yolk was shown to be in the alcohol-soluble fraction. Attempts to identify the active material with any known lipid have to date been unsuccessful. In the screening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

1966
1966
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 4 publications
0
38
0
1
Order By: Relevance
“…Indeed, the anti-inflammatory properties of PEA were first described over fifty years ago (Coburn et al, 1954) and are well established Costa et al, 2002;De Petrocellis et al, 2001;Di Marzo et al, 2001b;Lo Verme et al, 2005a;Mazzari et al, 1996;Re et al,2007). PEA does not bind to CB 1 or CB 2 receptors (Di Marzo et al, 2001b;Lambert and Di Marzo, 1999;Lambert et al, 2002), however, SR144528 has been found to block the anti-edema effects of PEA that is administered before carrageenan Lichtman et al, 2004;Malan et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the anti-inflammatory properties of PEA were first described over fifty years ago (Coburn et al, 1954) and are well established Costa et al, 2002;De Petrocellis et al, 2001;Di Marzo et al, 2001b;Lo Verme et al, 2005a;Mazzari et al, 1996;Re et al,2007). PEA does not bind to CB 1 or CB 2 receptors (Di Marzo et al, 2001b;Lambert and Di Marzo, 1999;Lambert et al, 2002), however, SR144528 has been found to block the anti-edema effects of PEA that is administered before carrageenan Lichtman et al, 2004;Malan et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The potential benefit of FAEs first came to the light in 1943 when Coburn & Moore [141] reported on the antipyretic properties of dried chicken egg yolk in children with rheumatic fever. A decade later, this same group identified the lipid fraction from egg yolk as the component responsible for this effect [142], with PEA being the active component [143]. The therapeutic applications of this lipid amide remained largely overlooked, however, until the emerging characterization of its antiinflammatory [144], analgesic [145] and anti-convulsant [146] properties.…”
Section: Microglia and Mast Cells As Therapeutic Targetsmentioning
confidence: 99%
“…In a continuation of this research, it was demonstrated that lipid fractions purified from egg yolk (Coburn et al, 1954;Long and Martin, 1956), as well as peanut oil and soybean lecithin (Long and Miles, 1950), exerted anti-allergic effects in the guinea pig (see Fig. 2 for a timeline of events).…”
mentioning
confidence: 99%